Penentuan Umur Bercak Darah Manusia pada Kain Katun dengan Menggunakan High Performance Liquid Chromatography - Mohammad Tegar Indrayana; Wibisana Widiatmaka; Ade Firmansyah Sugiharto; Ridla Bakri (Fakultas Kedokteran Universitas Riau, 2014)
This research is to study the method in determining the age of human bloodstain due the rarity of human bloodstainresearches in Indonesia, by analyzing the X and Y peaks that appeared in High Performance Liquid Chromatography(HPLC). This research is experimental with time series for 11 days observation by exposing the bloodstain onto 33pieces of cotton fabric, each measuring 1 cm x 1 cm that originated from 3 respondents with environmental conditionsof the FKUI/RSUPN Dr. Cipto Mangunkusumo Forensic and Medico-legal Department which represents the area ofCentral Jakarta. The results of this research is the X and Y peaks do not point to a linearity so that the criteria for linearregression equation is not met. The conclusion of this research is age of human bloodstain on cotton fabric byanalyzing X peak with HPLC cannot yet be used pragmatically in the field in accord to the conditions at the crimescene.